Preprogrammed, Parallel On-Chip Immunoassay Using System-Level Capillarity Control - Kim, Sung-Jin (2013)
Fully manual use of conventional multiwell plates makes enzyme-linked immunosorbent assay (ELISA)-based immunoassays highly time-consuming and labor-intensive. Here, we present a capillarity-driven on-chip immunoassay that greatly saves time and labor with an inexpensive setup. Our immunoassay process starts with pipetting multiple solutions into multiwells constructed on a microfluidic device chip. Subsequently, capillarity spontaneously transports multiple sample solutions and common reagent solutions into assigned detection channels on the chip in a purely passive and preprogrammed manner. Our device implements capillarity-driven immunoassays involving four sample and six reagent solutions within 30 min by orchestrating the functions of on-chip passive components. Notably, our immunoassay technique reduces the total number of pipetting processes by ~5 times, as compared to assays on multiwell plates (48 vs 10). This assay technique allows us to quantify the concentrations of C-reactive protein and suppressor of tumorigenicity 2 with a detection limit of 8 and 90 pM, respectively. This device should be useful for sophisticated, parallel biochemical microfluidic processing in point-of-care settings under limited resources. [Image: see text]